SURVEY OF PTH, CANXIUM, PHOSPHORUS, AND HEMOGLOBIN CONCENTRATIONS IN PATIENTS WITH CHRONIC KIDNEY DISEASE TREATED BY PERITONEAL DIALYSIS AND PERIODIC HEMODIALYSIS (Vietnam Journal of Community Medicine, 2026)
Objective: To survey biochemical parameters, including parathyroid hormone, canxium, phosphorus, and hemoglobin in patients with end-stage renal disease undergoing either hemodialysis or peritoneal dialysis, to evaluate the effectiveness of mineral metabolism control and anemia management according to KDIGO (2012) guidelines.Subjects and methods: A cross-sectional descriptive study was conducted on 185 patients at the Department of Nephrology - Dialysis, Thong Nhat Hospital, comprising 57 on peritoneal dialysis and 128 on hemodialysis, from November 2022 to October 2024. Biochemical parameters were analyzed and compared between the 2 groups using appropriate statistical methods.Results: There was no statistically significant difference between the hemodialysis and peritoneal dialysis groups in any of the parameters (parathyroid hormone, canxium, phosphorus, hemoglobin). Peritoneal dialysis showed better phosphorus control than hemodialysis with a median 1.5 mmol/L (1.09-1.91) vs. 1.75 mmol/L (1.375-2.125), p < 0.05). A mild positive correlation between parathyroid hormone and hemoglobin was observed in the peritoneal dialysis group (rho = 0.268; p < 0.05). Achievement rates according to KDIGO (2012) targets: parathyroid hormone ~60%, canxium > 50%, hemoglobin > 33%, phosphorus lowest (10.7-15.8%), Ca × P > 98%.Conclusion: Both dialysis modalities demonstrated comparable effectiveness in controlling biochemical parameters according to KDIGO (2012) guidelines. Peritoneal dialysis demonstrated superior phosphorus removal and may offer benefits for improving anemia status.
Keywords: Parathyroid hormone, hemodialysis, peritoneal dialysis, end-stage chronic kidney disease.